INOVASI PENGOLAHAN BELIMBING MANIS MENJADI BERBAGAI PRODUK OLAHAN PANGAN KREATIF - Azelia monica azizu; Wa Ode Al Zarliani; Wa Ode Dian Purnamasari; Abdul Hadi Bone; Safrin Edy (LPPM Universitas HKBP Nommensen, 2023)
Bungi sub-district is one of the sub-districts where many people plant sweet star fruit in their yards. Efforts to diversify processed star fruit products have not received much public attention. This is because star fruit has perishable constraints with a short shelf life, making the fruit have low economic value. The purpose of this activity is to create new products from processed starfruit, which is expected to provide benefits to the community as new innovations in processing, and can increase the selling value of starfruit from the previous period. In addition, training activities with local residents provide new knowledge that can be applied independently by farmers and the community in developing optimal business. Community service is held in June. The location of the community service activities is in Bungi District, Baubau City, as the center for producing star fruit. Community assistance activities regarding the manufacture of processed star fruit can increase economic income and form women's hydroponic farmer groups